The Use of Mine Sequencing Controlled Through Numerical Modelling and Instrumentation to Destress a Highly Burst Prone Sill Pillar - Draft (Canadian Institute of Mining, Metallurgy and Petroleum, 2005)
In order to maintain a production rate of 6,000 tonnes per day from underground at the Williams Operating Corporation, two independent mining areas were required which created a long narrow sill pillar between them. During initial mining of the sill pillar there were a number of significant ground falls [LeBlanc and Murdoch, 2000] and in March 1999, with no active mining ongoing in the sill pillar area, a rockburst of magnitude 3.0 Nuttli occurred. Extensive ground support was designed and installed to withstand events of similar magnitude [Bawden and Jones, 2002]. A mine wide microseismic system was installed to monitor mine induced seismic behaviour over the entire mine. The area most directly affected by the 1999 rockburst was rehabilitated using a highly ductile support design. Along with microseismic instrumentation, the areas were instrumented using conventional SMART Cables and SMART MPBX?s. Subsequent to this, the area was impacted by a large number of high magnitude seismic events [magnitudes between 1.7 and 3.5 Nuttli]. The ground support performed very well during these events, providing confidence in the mine?s ability to control the ground under severe rockburst conditions. Analyses of microseismic and conventional instrumentation, combined with numerical analyses of sequence alternatives, were used to develop an optimal mining strategy for the sill pillar area. The selected strategy involved utilization of instrumentation data and calibrated model results to analyze yield zones in the sill. The analyzed ?yielded? zones were assessed to be low seismic risk. Initial mining in the sill was then concentrated in these low risk areas, with the objective of further concentrating stress into the remaining seismically active area, in order to induce ultimate failure of the sill. Continuing large magnitude seismicity and resulting damage in the remaining ?high seismic risk? area, led to abandoning a second portion of the footwall access and the strategic decision to extract a stope near the centre of this zone in order to force final failure of the sill pillar. During execution of this plan two large magnitude seismic events occurred resulting in destressing and final failure of the remaining sill pillar. The paper provides a detailed description of this ?strategic mine sequence driven self-destressing process? and the implications to final extraction planning in this area of the mine.